O Professor que desenvolve Modelagem Matemática na Educação Básica no Estado do Paraná - Cararo, Elhane de Fátima Fritsch (2022)
Mathematical Modeling has drawn the attention of researchers and teachers who teach Mathematics at all levels of education and this can be seen through publications in events and periodicals in the area, in themes of theses and dissertations. However, the researches that question this “who does” Mathematical Modeling are still limited. Our research question: Who is this “who” that develops Mathematical Modeling in Basic Education in the State of Paraná? sought to understand, in a phenomenological and hermeneutic perspective, who is this “who” who develops Mathematical Modeling as a subject, being-in-the-world, person, individual and citizen. We emphasize that our search is not just for the specific profiles of these teachers, but for the understanding of what moves these teachers to develop Mathematical Modeling in Basic Education. Directed by the phenomenological way of proceeding, in a movement of going-to-the thing-itself, experiencing how it manifests itself, we were building the path of research. This path was making sense and showing itself to researchers from the complicity between the interrogation, the research methodology, the interrogated and their surroundings. We chose to present our research in the multipaper format, a format that will enable access to the research results not as a part, but as a whole that represents the tread in search of meaning and understanding of this “who”, who develops Modeling. The thesis is composed of three articles that show our path towards what is shown in a phenomenological and hermeneutic movement. The first article exposes the presence of teachers who teach Mathematics in Basic Education at the National Conference on Mathematical Modeling in Mathematics Education, which led us to look at Mathematics teachers from the State education network of Paraná as significant subjects of the research that composes the third article. The second article discusses in a philosophical and hermeneutic way who is this who develops Mathematical Modeling, in a philosophical perspective and opens the understanding of this who as a subject, person, individual and citizen. The third article stems from the field research, which has as significant subjects 27 teachers of Basic Education in the State of Paraná, who teach Mathematics with Modeling. The article discusses who is this who, through the testimony of those who teach Mathematics with Modeling, exposes the five categories that emerged from the analyzes and interpretations of these testimonies, leading us to the understanding that it is the directive force of the formation of this who that leads the teacher to develop Mathematical Modeling. The Atlas.Ti. software was the support tool for the phenomenological analyzes and interpretations performed by the researcher.